A shortened version of the Dementia Drivers’ Screening Assessment - Lincoln, Nadina; Radford, Kathryn A. (Mark Allen Healthcare, 2014)
Introduction: Cognitive tests are used to inform recommendations about the safety of people with dementia to continue driving. The Dementia Drivers’ Screening Assessment (DDSA) is a neuropsychological battery designed to assist in this process. However, it is lengthy to administer and requires materials from various test batteries. Aims: The primary aim of this study was to develop a shortened version of the DDSA for individuals with dementia. Methods: Data on participants with dementia from two studies were analysed. These participants were all drivers with dementia who were identified by community mental health teams and psychiatrists. Each participant was assessed on the DDSA and also assessed on-road by an ‘approved driving instructor’ using the Nottingham Neurological Driving Assessment. Results: This study analysed 102 participants, who had a mean age of 74.0 (SD=7.7) years and of whom 80 (78%) were men. Twenty three drivers were judged to be unsafe and 79 safe. The agreement between the short version and on-road assessment was 79%. The assessment was better at detecting safe drivers than unsafe drivers. Conclusion: The findings suggested that the shortened DDSA is suitable for participants who are unable or do not wish to undergo lengthier assessment.